(3JPcQI Phj GdBOGH aj TQM edMI GdEYQGHs - (3CHheMeO GdbGSe Hf Ydj Hf eMeO Hf YKeGf GdMQjQj GdHUQjs; (3GdMQjQj,J (B516 (3g` s
(3ChdgG (B:s
(3Cbhd ef HYO GaJJGM Gdbhd HMeO Pj GdWhd GdTOjO GdMhd s
(3BNQgG (B:s
(3aGfXQ EdjgG fXQ GdeSJMSf hMSf GdXf HgG hCMSf JeJ edMI GdEYQGH HTQMgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQ GdLRA GdChd (B33 (3fMhs
(3HgG fXGe GdJYbjHIs
(3ajgG VHWs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdfMhs